Satisfação e insatisfação no casamento : os dois lados de uma mesma moeda ? - Machado, Luciane Medeiros (2007)
Marital relationship is the most intimate among the relations, bringing within several particularities that make this issue a rich and never-ending source of information about human nature. The general purpose of this work was to identify husband behaviors responsible to the satisfaction and dissatisfaction of their women. With these results, we tried to analyze similarities and differences between behaviors, in order to verify the possibility of two dimensions, one for satisfaction and other for marital dissatisfaction. The sample was composed by 103 married women, average age of 16 years old, with one or two children, being the majority catholic, that usually go to their church, with an educational level corresponding to completed middle school, and working in several activities, with a salary between R$300.00 and R$900,00. Women were found at their residences, schools and at work location. After being notified about the objectives of the study and agree in participating of it, they were individually interviewed, with the support of a questionnaire developed for this. For data collection, the Critical Incident Technique was used, consisting in getting reports of positive and negative occurrences, and to select the critical situations and behaviors. The questionnaire was composed by two questions on critical incidents, one for the positive incident and other for the negative one, plus four questions about frequent husband behaviors responsible for positive feelings on the women: happiness and love, and for negative feelings: sad/unhappiness and angry. After content analysis, we obtained 124 positive critical incidents and 105 negative ones, which were classified at 11 categories by the situation that they occurred, being day-to-day the most frequent.The results showed that the more frequent positive critical incident refers to: support, protect and care about the wife, to gift and go out or have a trip together. The negative critical incidents included: to offend, to hurt, making important decisions and not consulting the wife, being with other women and to be drunk.The analysis of those behaviors revealed that the ones related to satisfaction were different of those related to marital dissatisfaction, with the exception of supporting, protecting and caring about the wife, and its opposite, not to support. These results suggest two dimensions, one composed by the satisfaction s factors and another one about dissatisfaction, and this hypothesis might be confirmed by others studies and methods. About the husband s habitual behaviors related to happiness and love feelings, being: affective, caring, going out with her and to gift or to prepare a party point out among others.The habitual behaviors that lead to sadness and angry feelings refer specially to: demonstrate negative attitudes and emotions, not talking with her, not speaking too much or anything, and husband s addictive behaviors as drinking, gambling or smoking. When the critical behaviors were compared with the habitual behaviors, similarities were found, but also important differences, so that in day-by-day they must help with the housekeeping, talking with her, and to demonstrate positive attitudes and emotions, while in critical and extreme situations it is important to support, protect and care about the well-being of the wife, being negative to offend, to hurt, ant to cheat. These results suggest that it isn t enough to act in a positive way but is also important not to show negative behaviors so the relationship is not harmed.